Integrating Local Wisdom in E-LKPD: Enhancing Students' Critical Thinking Skills - Rahmawati, Novita; Agnafia, Desi Nuzul; Rohmani, Lucky Amatur (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to develop E-LKPD based on CTL containing local wisdom of Ngawi with the help of the liveworksheet website to train students’ critical thinking skills. Methodology: The research design used by the researcher is R&D research. The development procedure used is the 4D development model (Define, Design, Develop, Disseminate). The trial subjects were class VII D, VII E, and teachers at MTs Negeri 9 Ngawi. Main Findings: The results of the study showed that the CTL-based E-LKPD had high feasibility, with validation results from material experts of 91% (very feasible), language experts of 76.3% (feasible), and media experts of 91.7% (very feasible). Practicality tests from students and teachers showed positive responses with a very practical category (95% and 91.4%). In addition, the analysis of effectiveness based on learning outcomes showed a significant increase in critical thinking skills of students in the experimental class compared to the control class (p value <0.05). Novelty/Originality of this study: E-LKPD integrates Ngawi’s local wisdom, namely Seloondo tourism as a learning resource, so that it not only improves students’ critical thinking skills, but also instills ecological awareness and local culture. In addition, the use of the Liveworksheet website makes E-LKPD more interactive, flexible, and innovative than conventional LKPD.